A Dynamic Ultra-Capacitor Model for Vehicular Applications - Vural, B.; Uzunoglu, M.; Erdinc, O.; Onar, O. C. (IEEE, 2009)
Ultra-capacitor (UC) models capture the characteristics of real-life UCs, and can he used to predict their behavior under various operating conditions. In this paper, a dynamic model of UC that can be useful for vehicular applications has been developed using MATLAB/Simulink (R). Dynamic simulations are carried out to obtain the changes in UC terminal output voltage under different charge/discharge rates and temperature conditions. Then, the simulation results are verified compared with the results obtained from experimental studies. Comparisons show that the model is effective and operational.
Keywords: Ultra-capacitor; dynamic model; vehicular application; POWER; ULTRACAPACITORS; OPTIMIZATION; MANAGEMENT; Engineering